Sustained Release of Transforming Growth Factor-β1 from Platelet-Rich Chondroitin Sulfate Glycosaminoglycan Gels - Birdwhistell, Kate E.; Karumbaiah, Lohitash; Franklin, Samuel P. (The Journal of Knee Surgery, 2018)
Activated platelet-rich plasma (PRP), also referred to as platelet-rich fibrin (PRF), has been used to augment numerous techniques of cartilage repair in the knee but does not always result in superior quality of repair tissue. One possible reason that PRF does not consistently result in excellent cartilage regeneration is the transiency of growth factor provision with PRF. The objective of this study was to compare the release of transforming growth factor (TGF)-β1 from PRF and from PRP combined with a novel chondroitin sulfate glycosaminoglycan (CS-GAG) gel. PRP was prepared from nine healthy dogs and split into two aliquots: one activated with bovine thrombin and calcium chloride (CaCl2) to form PRF and the other aliquot was used to rehydrate a lyophilized CS-GAG gel. Both PRF and the CS-GAG gels were incubated in media for 13 days and media were collected, stored, and replaced every 48 hours and the concentration of TGF-β1 quantified in the media using an enzyme-linked immunosorbent assay. Concentrations of TGF-β1 in the media were up to three times greater with the CS-GAG gels and were significantly (p < 0.05) greater than with PRF on days 3, 5, 7, 9, and 13. Furthermore, TGF-β1 elution was still substantial at day 13 with the use of the CS-GAG gels. Additional in vitro work is warranted to characterize TGF-β1 elution from this CS-GAG gel with human PRP and to determine whether the use of these CS-GAG gels can augment cartilage repair in vivo.
Keywords: transforming growth factor-β1; chondroitin sulfate glycosaminoglycan; platelet-rich plasma; hydrogels; platelet-rich fibrin